EMPLOYMENT OF HOSPITALITY GRADUATES: THE CHALLENGES - Zatul Iffah Mohd Fuza; Wan Nor Bayah Wan Kamarudin; Amanina Mat Ghani; Wan Nazriah Wan Nawawi (Journal of Islamic, Social, Economics and Development, 2022)
Although Malaysiaâ€™s Higher Education Institutions (HEIs) have recently produced a significant number of graduates, there are now marginally fewer that get employed, particularly hospitality graduates. Therefore, this study investigated the employability challenges of hospitality graduates found in the literature. Secondary data was obtained from multiple platforms using key search terms, namely â€œemployabilityâ€, hospitality graduateâ€, and â€œgraduate employabilityâ€. Content analysis was used for the literature review. The finding reveals that the challenges revolve around skill, curriculum, attitude, qualification, interest, and the hospitality industry environment. Of the six themes, challenge, skill, and curriculum were the most prominent ones in the literature. This review emphasized the challenges of employability, not only regarding the graduate attributes, but also the curriculum program and the nature of the hospitality industry. Also, a significant information gap emerged that must be addressed. This study could serve as a reference for managing the employability of hospitality graduates in the future.